2019
DOI: 10.1002/ams2.403
|View full text |Cite
|
Sign up to set email alerts
|

Intentional or unintentional drug poisoning in elderly people: retrospective observational study in a tertiary care hospital in Japan

Abstract: Aim Intentional or unintentional acute drug poisoning occurs even in elderly people, but little is known about the factors influencing the intention to poisoning. A retrospective study was undertaken to describe the characteristics of acute drug poisoning in elderly people according to whether the poisoning was intentional or unintentional and the responsible agents. Methods The study was carried out in a single tertiary hospital in Japan. A total of 145 patients aged ≥65 years who were transferred by an ambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…OAM can also involve the administration of inappropriate substances, inappropriate doses of medications, or failure to monitor drug therapy, which contributes to an increased risk of intoxications [ 40 ]. Although intoxications are mostly unintentional in older adults, there is an increased prevalence of intentional intoxications in the victims of OAM compared to their non-maltreated peers [ 41 ], which is in line with our findings (the intoxication rate was 1.7 times higher in the suspected victims— Table 3 ). Additionally, in these cases, we were not able to determine its medico–legal aetiology.…”
Section: Discussionsupporting
confidence: 91%
“…OAM can also involve the administration of inappropriate substances, inappropriate doses of medications, or failure to monitor drug therapy, which contributes to an increased risk of intoxications [ 40 ]. Although intoxications are mostly unintentional in older adults, there is an increased prevalence of intentional intoxications in the victims of OAM compared to their non-maltreated peers [ 41 ], which is in line with our findings (the intoxication rate was 1.7 times higher in the suspected victims— Table 3 ). Additionally, in these cases, we were not able to determine its medico–legal aetiology.…”
Section: Discussionsupporting
confidence: 91%
“…Unintentional drug poisoning occurs more often than intentional drug poisoning. Whereas in young adults, the majority of drug poisoning cases is intentional (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding old age poisoning; Haoka et al (2019) reported that the majority of unintentional poisoning was in older than 75 years. This is because elderly are multiple drug user as well as the distribution, excretion and sensitivity to drugs change with age.…”
Section: Discussionmentioning
confidence: 99%